SOCIETY AND THE INDIVIDUAL: ON THE GROUNDS OF LIMIT OF BEING HUMAN - Nikolay Andreevich Makovsky; Mariya Igorevna Durneva (Современная наука и инновации)
The article is devoted to the analysis of society, as a direct human existence. The authors attempted to substantiate the conceptual position that the key actors are the bearers of social relations society and the individual, the interaction between them is due to the presence of the relevant factors, manifested in various forms.